2011
DOI: 10.1111/j.1529-8019.2011.01441.x
|View full text |Cite
|
Sign up to set email alerts
|

Finasteride, 1 mg daily administration on male androgenetic alopecia in different age groups: 10-year follow-up

Abstract: Finasteride 1 mg is indicated for the treatment of men with androgenetic alopecia (AGA). However, more than 5 years efficacy and safety has not been previously reported. To assess the efficacy over 10 years in different age groups of men with AGA. 118 men, between 20 and 61 years, with AGA receiving finasteride (1 mg/day), were enrolled in this uncontrolled study. Efficacy evaluation was assessed with standardized global photographs at T0,T1,T2,T5,T10. Statistical analysis was made using frequency tables and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 14 publications
(30 reference statements)
3
58
3
2
Order By: Relevance
“…Study population ethnicity was composed of 582 individuals of white race (64.1%), 182 subjects of pardo race (brown multiracial individuals, 20.0%), 122 individuals of black race (13.4%), 16 CI 1.44-2.61, P <.001) were significantly associated with moderate to severe LUTS. Conversely, a BMI !30 (P ¼ .85) and waist circumference (P ¼ .64) were not associated with LUTS.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Study population ethnicity was composed of 582 individuals of white race (64.1%), 182 subjects of pardo race (brown multiracial individuals, 20.0%), 122 individuals of black race (13.4%), 16 CI 1.44-2.61, P <.001) were significantly associated with moderate to severe LUTS. Conversely, a BMI !30 (P ¼ .85) and waist circumference (P ¼ .64) were not associated with LUTS.…”
Section: Resultsmentioning
confidence: 99%
“…29 Furthermore, drugs that inhibit 5 alpha-reductase are shown to be effective in the treatment of both LUTS and AGA. [16][17][18] Initial studies have suggested an association between the incidence of LUTS and AGA in older patients. However, these were conducted with smaller cohorts and not adjusted for relevant demographic predictors.…”
Section: Commentmentioning
confidence: 98%
See 2 more Smart Citations
“…Finasteride is a competitive antagonist to type II 5α-reductase which blocks conversion of testosterone to dihydrotestosterone, resulting in improvements in androgenic alopecia at the expense of partial systemic androgen blockade. Response rates with long-term (10 years) therapy are around 50% 11 . Overall, despite considerable research in this area, there is still no adequate therapy for hair loss.…”
Section: Introductionmentioning
confidence: 99%